Significance of the gut tract in the therapeutic mechanisms of polydopamine for acute cerebral infarction: neuro-immune interaction through the gut-brain axis - Xu, Feng-Hua; Sun, Xiao; Zhu, Jun; Kong, Ling-Yang; Chang, Yuan; Li, Ning; Hui, Wen-Xiang; Zhang, Cong-Peng; Cheng, Yi-Ming; Han, Wen-Xin; Tian, Zhi-Min; Qiao, Yan-Ning; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundRecent research has made significant progress in elucidating gastrointestinal complications following acute cerebral infarction (ACI), which includes disorders in intestinal motility and dysbiosis of the gut microbiota. Nevertheless, the role of the gut (which is acknowledged as being the largest immune organ) in the immunoreactive effects of polydopamine nanoparticles (PDA) on acute ischemic stroke remains inadequately understood. In addition to its function in nutrient absorption, the gut acts as a protective barrier against microbes. Systemic immune responses, which are triggered by the disruption of gut barrier integrity, are considered as one of the mechanisms underlying acute ischemic stroke, with the gut-brain axis (GBA) playing a pivotal role in this process.MethodsIn this study, we used a PDA intervention in an ACI model to investigate ACI-like behavior, intestinal barrier function, central and peripheral inflammation, and hippocampal neuron excitability, thus aiming to elucidate the mechanisms through which PDA improves ACI via the GBA.ResultsOur findings indicated that as ACI mice experienced dysbiosis of the gut microbiota and intestinal barrier damage, the levels of proinflammatory factors in the serum and brain significantly increased. Additionally, the activation of astrocytes in the hippocampal region and neuronal apoptosis were observed in ACI mice. Importantly, our study is the first to provide evidence demonstrating that PDA effectively suppresses the neuroimmune interactions of the gut-brain axis and significantly improves intestinal epithelial barrier integrity.ConclusionWe hope that our discoveries will serve as a foundation for further explorations of the therapeutic mechanisms of PDA in ACI, particularly in elucidating the protective roles of gut microbiota and intestinal barrier function, as well as in the development of more targeted clinical interventions for ACI.